2011
DOI: 10.1159/000330489
|View full text |Cite
|
Sign up to set email alerts
|

Application of Dermal Microdialysis for the Determination of Bioavailability of Clobetasol Propionate Applied to the Skin of Human Subjects

Abstract: Dermal microdialysis was used to assess the bioavailability of a topical corticosteroid, clobetasol propionate, following application onto the skin of human subjects. The penetration of clobetasol propionate from a 4% m/v ethanolic solution applied onto 4 sites on one forearm of healthy human volunteers was studied. A lipid emulsion, Intralipid®, was used as the perfusate and linear microdialysis probes with a 2-kDa cutoff were inserted intradermally at the designated sites. The results indicated that Intralip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(15 citation statements)
references
References 55 publications
2
13
0
Order By: Relevance
“…The identification of probe depth as a relevant variable indicated that the overall methodological variation of dOFM is low. Although the influence of probe depth on kinetics has repeatedly been considered in dermal MD studies ( 15 , 18 ), no significant effect has been published yet. Methodological differences or the different distribution of predominantly water soluble compounds which have been investigated in these dermal MD studies could have prevented the identification of any impact of probe depth variations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The identification of probe depth as a relevant variable indicated that the overall methodological variation of dOFM is low. Although the influence of probe depth on kinetics has repeatedly been considered in dermal MD studies ( 15 , 18 ), no significant effect has been published yet. Methodological differences or the different distribution of predominantly water soluble compounds which have been investigated in these dermal MD studies could have prevented the identification of any impact of probe depth variations.…”
Section: Discussionmentioning
confidence: 99%
“…One study performed by Au et al . ( 15 ) investigated the feasibility of CP-17 sampling in the skin, but they applied highly concentrated CP-17 in ethanolic solution, because the high lipophilicity of CP-17 ( LogP = 3.49) precluded the use of a commercial formulation for MD sampling. A study on the penetration behavior of a topical lipophilic drug into healthy and psoriatic lesional skin using tape-stripping followed by skin punch biopsy was performed by Rony et al .…”
Section: Introductionmentioning
confidence: 99%
“…In particular, miconazole induces a strong phosphorylation of ERK1/2, whose constitutive activation has been correlated with a profound increase in the extent of remyelination after toxin-induced demyelinating injury [53,59]. In addition, clobetasol, an agonist of glucocorticoid receptor widely used to treat different pathological skin conditions [60], can also act through the smoothened (Smo) receptors [61], whose activity is regulated by cholesterol intermediates [57,58]. As reported below, the efficacy of all these drugs in enhancing OL differentiation has been well documented by several publications and, in the case of clemastine, also by two clinical trials on MS patients.…”
Section: Drugs Promoting Remyelination Through a Potential Action On mentioning
confidence: 99%
“…This technique allows continuous sampling during topical drug delivery [15, 18,19]. This sensitive tool has been used to assess local bioavailability of topically delivered drugs in humans [20][21][22], including iontophoretically administered compounds [23] (Figure 2).…”
Section: Pharmacokineticsmentioning
confidence: 99%